Analysis of dose using CBCT and synthetic CT during head and neck radiotherapy: A single centre feasibility study. (June 2020) - Hay, Lisa K; Paterson, Claire; McLoone, Philip; Miguel-Chumacero, Eliane; Valentine, Ronan; Currie, Suzanne; Grose, Derek; Schipani, Stefano; Wilson, Christina; Nixon, Ioanna; James, Allan; Duffton, Aileen
Highlights: Dose calculations between synthetic CT and planning CT acquired at the same treatment fraction have small differences. The safe omission of repeat CT during H&N RT is feasible when CBCT is available. Synthetic CT verification appears to overestimate the need to re-plan, therefore not putting patients at risk. Repeat CT should be used for replanning, being guided by CBCT and synthetic CT. Abstract: Objectives: The study aimed to assess the suitability of deformable image registration (DIR) software to generate synthetic CT (sCT) scans for dose verification during radiotherapy to the head and neck. Planning and synthetic CT dose volume histograms were compared to evaluate dosimetric changes during the treatment course. Methods: Eligible patients had locally advanced (stage III, IVa and IVb) oropharyngeal cancer treated with primary radiotherapy. Weekly CBCT images were acquired post treatment at fractions 1, 6, 11, 16, 21 and 26 over a 30 fraction treatment course. Each CBCT was deformed with the planning CT to generate a sCT which was used to calculate the dose at that point in the treatment. A repeat planning CT2 was acquired at fraction 16 and deformed with the fraction 16 CBCT to compare differences between the calculations mid-treatment. Results: 20 patients were evaluated generating 138 synthetic CT sets. The single fraction mean dose to PTV_HR between the synthetic and planning CT did not vary, although dose to 95% of PTV_HR was smaller at week 6 compared to planning (difference 2.0%, 95% CI (0.8 to 3.1), p = 0.0). There was no statistically significant difference in PRV_brainstem or PRV_spinal cord maximum dose, although greater variation using the sCT calculations was reported. The mean dose to structures based on the fraction 16 sCT and CT2 scans were similar. Conclusions: Synthetic CT provides comparable dose calculations to those of a repeat planning CT; however the limitations of DIR must be understood before it is applied within the clinical setting.